Keberhasilan Proses Pendidikan Karakter Terdapat di Pundak Pendidiknya - Putu Subawa (UHN IGB Sugriwa Denpasar, 2015)
Educators important figure in character education course caused by its presence as a central figure in education. Good educator of character is when he does not care about him as long as he could see their students grow and thrive. Character educators on assessed from nature sincere, patient, and full commitment to establish soul didiknya.Peningkatan welfare participants would not quite able to change the quality of teachers and education if it is not accompanied by changes in educational culture and spirit of education. Increased prosperity will not be quite capable of changing the quality of teachers and education if it is not accompanied by changes in educational culture and spirit of education. Personality and character pendidiki must be strong so that he was not brought on by a situation that makes his personality defeated by circumstances. Strong personality and unwavering needed to create a role that also serves to form the personality of learners. Progressive educator is an educator who serves as a motivator. Its function is to make students believe that they can change, they are engaged and motivated that the learning process gives them the understanding and skills which can make the face of the world.